Reference range for the fetal intracranial translucency measurement between 11 and 14 + 2 weeks of gestation in a Brazilian population. (17th August 2016) - Peixoto, Alberto Borges; Caldas, Taciana Mara; Lasmar, Larrisa Abu; Martins, Wellington P.; Pares, David Baptista; Araujo Júnior, Edward
Abstract: Objective : To establish a reference range for the fetal intracranial translucency (IT) measurement between 11 and 14 + 2 weeks in a Brazilian population. Methods : A retrospective cross-sectional study was performed with 199 low-risk singleton pregnancies during the first trimester ultrasound exam. The IT (fourth ventricle width) measurement was performed in a mid-sagittal view of fetal profile defined by two echogenic borders – the dorsal part of the brain stem anteriorly and the choroid plexus of the fourth ventricle posteriorly. Polynomial regression was used to obtain the best fit using fetal IT measurements and crown-rump length (CRL). Percentiles 5th, 50th and 95th were determined for each gestational age. Results : The mean of fetal IT ranged from 1.6 mm at CRL 45 to 2.0 mm at CRL 84 mm. A best fit curve was a first-degree polynomial regression: IT measurement = 1.001 + 0.0124 × CRL ( R 2 =0.09). Conclusion : Reference range for the fetal IT measurement between 11 and 14 + 2 weeks of gestation in a Brazilian population was established.